Sosialisasi dan Edukasi Green Human Resource Management pada Pengrajin Aluminium di Desa Tanjung Atap Barat - M Oktarianto; Heriyanto Heriyanto; Fitriasuri Fitriasuri; Andrian Noviardy; Dina Mellita; Efan Elpanso (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2025)
Socialization and education about Green Human Resource Management (GHRM) are important to be implemented in MSMEs, especially in the aluminum craft sector, to encourage environmental desire and efficiency. In Tanjung Atap Barat Village, most aluminum craftsmen still use practices that are less environmentally friendly, such as less than optimal waste management and the use of raw materials that are not fully based on recycling. Therefore, a GHRM approach is needed that integrates the principle of desire through increasing the ability, motivation, and opportunities for craftsmen to contribute to preserving the environment. This study aims to understand and analyze the implementation of Green Human Resource Management (GHRM) in aluminum craft MSMEs in Tanjung Atap Barat Village, with a focus on preserving human resources that support environmental sustainability. The method used in this study consists of three main stages: socialization, education, and evaluation. The results of this study indicate that the socialization and education of Green Human Resource Management (GHRM) carried out on aluminum craftsmen in Tanjung Atap Barat Village with the ability-motivation-opportunity (AMO) approach successfully introduced GHRM principles such as energy efficiency, use of recycled materials, and waste management.